Improving Tadris Bahasa Inggris Students’ Competency of Curriculum Development in Language Education through Investigating SMU Teachers’ Perceptions on the Implementation of 2013 Curriculum - Indrawati Indrawati (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
Practicum Teaching has never been easy for most students. They have to undergo many courses before having the real practicum teaching. Balancing between the performance and competence finally is not totally a piece of cake in terms of real teaching. Lacks of skill in designing lesson plans, creating teaching material and managing classroom are occasionally become e great obstacle for pre-service teachers. And what makes it worse is they do not know well about the implementation of K-13 in teaching English in high schools. As a new implemented curriculum, pre-service teachers should struggle to apply this curriculum well in their teaching. This study investigates teachers‟ voices over K-13 and what strategies or approaches that teachers of English do to develop the quality of instruction in the classroom. Findings showed that mostly teachers of English are very welcome in implementing K-13 but in some conditions (for government to notice) , such as providing more trainings and bridging courses for teachers especially in suburbs, adding more free text books for unprivileged students, and so on.